2017
DOI: 10.18178/ijfe.3.2.127-131
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperature on the Physicochemical Properties of Tamarind (Tamarindus Indica) Powder

Abstract: The aim of the present investigation is to study the effect of temperature on the physicochemical properties of tamarind powder that produced by a double drum dryer. The temperatures varied from 120 to 140°C, whereas other parameters like drum clearance (0.0254 mm) and drum rotation speed (0.75 rpm) were kept constant. Drying yield, moisture content, pH value, total acidity, bulk density and solubility were analyzed for the powder samples. Higher temperature decreased the moisture content of the powder, but he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
1
0
0
Order By: Relevance
“…Increases in temperature consequently generated the vibrations in molecules, which led to the decreased tendency of hydrogen bonds, and thus, the observed decrease in pH in Kyoho seeds. Decreased pH values in our study corroborated the earlier findings reported byPrangpru, Treeamnuk, Jaito, Vanmontree, and Treeamnuk (2017). The WHC and swelling capacity exhibited no significant change with temperature in the range of 303.15-313.15 K, but increase in temperature (323.15-313.15 K) showed higher water holding and swelling capacities than that of 303.15 and 313.15 K. These results are in accordance with studies investigated byVega-Gálvez et al (2015), and they concluded that drying temperatures (323.15-363.15 K) could affect in increased and/or decreased water holding and swelling properties.…”
supporting
confidence: 93%
“…Increases in temperature consequently generated the vibrations in molecules, which led to the decreased tendency of hydrogen bonds, and thus, the observed decrease in pH in Kyoho seeds. Decreased pH values in our study corroborated the earlier findings reported byPrangpru, Treeamnuk, Jaito, Vanmontree, and Treeamnuk (2017). The WHC and swelling capacity exhibited no significant change with temperature in the range of 303.15-313.15 K, but increase in temperature (323.15-313.15 K) showed higher water holding and swelling capacities than that of 303.15 and 313.15 K. These results are in accordance with studies investigated byVega-Gálvez et al (2015), and they concluded that drying temperatures (323.15-363.15 K) could affect in increased and/or decreased water holding and swelling properties.…”
supporting
confidence: 93%